ASSESSMENT OF NATIONAL ECONOMIC SECURITY OF UKRAINE - Ganna Kozachenko; Andriy Didyk; Yuriy Pogorelov; Yuliia Romanovska; Maksym Marmura (Фінансово-кредитна діяльність: проблеми теорії та практики, 2025)
The purpose of the article is to build an assessing model for national economic security and to assess the national economic security of Ukraine during 2019–2021. The concept of national economic security is examined. Its relationship with the concept of state economic security is disclosed. Existing approaches to assess the economic security of the state are reviewed. Using epistemological contextualism by P. Unger for assessing national economic security is demonstrated and justified. Using index-based and indicator-based methods for this purpose is substantiated. Sources of provisioning national economic security are justified, serving as the basis for selecting indicators for assessing national economic security. Requirements for indicators to assess national economic security are suggested. For each of the identified sources of provisioning national economic security, a set of indicators is proposed, and for each such indicator, its selection is justified. The assessment time period is substantiated to eliminate the distorting influence of military actions against Ukraine on the assessment results. The qualitative interpretation of the values of each selected indicator is justified. Based on the calculated values of the proposed indicators for 2019–2021, visual linear profiles of Ukraine's national economic security have been constructed.